SMART-JaCaMo: an organization-based team for the multi-agent programming contest - Cardoso, Rafael C.; Krausburg, Tabajara; Baségio, Túlio; Engelmann, Débora C.; Hübner, Jomi F.; Bordini, Rafael H. (Annals of mathematics and artificial intelligence, 2018)
The Multi-Agent Programming Contest in 2017 expanded upon the Agents in the City scenario used in the 2016 edition of the contest. In the Agents in the City contest, two teams compete to accomplish logistic tasks in simulations using realistic city maps from OpenStreetMap. The new version of the scenario shifted emphasis to include jobs that require assembled items, new types of facilities, and larger teams, resulting in a significantly more complex scenario than before. In this paper, we describe the strategies used by our team, highlighting our adaptations and any new additions from our participation in the previous year. One such new addition, is that now we have fully explored the use of all three programming dimensions (agent, environment, and organization) found in JaCaMo, the multi-agent system development platform that we used to implement our team. We also provide some discussion and analysis on what we believe were some of our most influential matches.